Teaching Syntax through Stories: Integrating Digital Storytelling to Enhance English Language Skills - Utami, Ni Putu Cahyani Putri (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2026)
Traditional methods of teaching English syntax are often criticized for being decontextualized and failing to engage students, leading to a gap between grammatical knowledge and practical application. Digital storytelling presents a promising, narrative-based alternative, yet empirical evidence of its effectiveness specifically for syntax instruction remains scarce. This study aimed to investigate the effectiveness of integrating digital storytelling on students' syntactic competence compared to conventional methods and to explore students' perceptions of this pedagogical approach. A mixed-methods study with a quasi-experimental, pre-test-post-test design was conducted with 50 intermediate-level university students. The experimental group (n=26) received instruction via digital storytelling, while the control group (n=24) used conventional methods. Data were collected through a syntax test and a perception questionnaire and were analyzed using an Independent Samples t-test on gain scores and Thematic Analysis. The quantitative findings revealed that the experimental group achieved significantly higher learning gains in syntactic competence compared to the control group (p < .001). Qualitatively, the thematic analysis indicated that students perceived the digital storytelling method as highly effective for enhancing comprehension through context and for significantly increasing their motivation and engagement in learning grammar. The study concludes that digital storytelling is a highly effective and engaging pedagogical tool for teaching English syntax. It provides a validated framework for educators seeking alternatives to traditional drills and contributes important empirical evidence to the field of Technology-Enhanced Language Learning (TELL).